The role of cytokeratin 19 levels in the determination of endometriosis stages. (3rd October 2022) - Yildiz, Caglar; Caner, Armagan; Oksasoglu, Bugra; Misir, Sema; Yaylim, İlhan; Hepokur, Ceylan
Abstract: Objective/Aim: Endometrisosis, one of the most common gynecological disease, is characterized by the presence of endometriotic tissue outside of uterine cavity. The development and the validation of a simple blood biomarker specific and sensitive for endometriosis may facilitate the rapid and the accurate diagnosis of the disease and thus early treatment. Cytokeratin expression changes during epithelial differentiation and this expression is important for the modulation and the control of cell cycle regulation, tumor cell motility and apoptosis. Cytokeratin 19 (CK-19) is expressed in most simple epithelial cells and their malignant counterparts. The aim of this study is to investigate serum CK-19 expression levels in patients with endometriosis and to determine the diagnostic role of CK-19 levels in differentiating various stage of endometriosis. Methods: Ctytokeratin-19 expression and level were studied in 70 endometriosis patients and 50 volunteers by ELISA and RT-PCR. ROC analysis was performed by comparing all stages with each other and with the control group. Results: The CK-19 levels were significantly higher in the endometriosis groups than that of the control group by ELISA and RT-PCR. A significant ( p  < .05) difference was observed in endometriosis patients according to the stages. Conclusion: Based on our data, it suggests that Cytokeratin-19 may have a potential role in the development of endometriosis.